ANALISIS EFISIENSI POMPA SENTRIFUGAL PADA DESALINASI DENGAN PROSES REVERSE OSMOSIS: ANALYSIS OF CENTRIFUGAL PUMP EFFICIENCY IN DESALINATION WITH THE REVERSE OSMOSIS PROCESS - I Wayan Joniarta; Ade Aprilian Dika; Made Wijana (Energy, Materials and Product Design, 2024)
This study provides information for the desalination industry in an effort to improve the performance and efficiency of desalination systems using the reverse osmosis method. By paying attention to the factors that influence the efficiency of centrifugal pumps, the provision of clean water in areas experiencing a water crisis will be better. Reverse Osmosis (RO) is a system in desalination technology that is often used to replenish fresh water supplies. RO performance depends on the quality of sea water as the raw water source. RO works by utilizing osmotic pressure. Hydrostatic pressure which is greater than osmotic pressure is used to reverse the flow, thereby producing fresh water. RO utilizes a high-pressure pump process to flow seawater through a membrane polymer structure. In RO there is a main membrane module configuration which has two functions, namely supporting the performance of the RO membrane and providing efficient fluid management. The desalination system used at PT Perusahaan Air Indonesia America (PAIA) still uses centrifugal pumps and can produce a production capacity of 600-700 m3/day, and is still in the system upgrade stage. From the calculations that have been carried out, the pump efficiency value is 59.16%.